Knowledge and Attitude of the Mother in Maintenance of Dental Cleaning in Qurratul Ayyun Early Childhood Education at Banda Aceh City - Eka Sri Rahayu; Reca Reca (Science Midwifery, 2022)
Caries are the most common dental problem found in children. Dental caries is an infectious disease that is a progressive demineralization process in the hard tissues of the crown and root surfaces of the teeth that can be prevented. Based on the results of dental examinations on 35 children aged 3-5 years at Qurratul Ayyun early childhood education, it was found that 60% of children suffered from dental caries, and the average dental and oral hygiene of children in the kindergarten was the poor category with a score of 37, the data is still far from expectations. Because it is not following the government's stipulation that the dental and oral hygiene status score (PHP-M) is < 15, the role of the mother is very much needed in maintaining the child's dental and oral hygiene. This study aimed to determine the mother's knowledge and attitudes in maintaining oral and dental hygiene in terms of caries status in Qurratul Ayyun early childhood education, Banda Aceh City. The design of this research is descriptive quantitative research. The sample in this study is the total population of 35 student respondents. The study results showed that the mother's knowledge of the maintenance of dental and oral hygiene of Qurratul Ayyun early childhood education students in Banda Aceh City was poor, with 18 respondents (51.4%). Mother's attitude toward maintaining dental and oral hygiene of Qurratul Ayyun early childhood education students in Banda Aceh City was in the poor category with 18 respondents (51.4 %).